PEMODELAN BANGKITAN PERGERAKAN PADA PERUMAHAN CITRA PESONA INDAH DAN PERUMAHAN METRO PALU REGENCY DI KOTA PALU - Rahman, Rahmatang (Jurusan Teknik Sipil Universitas Tadulako, 2014)
Construction of residential area in Palu city increases along with the city development and population growth. It can raise or enlarge the trip generation both for medium residential (subsidized residential) and for middle to upper residential (the elite residential) and also affect the use of land as well as increased traffic. The purpose of this thesis is to determine the factors of affect trip generation and make the trip generation models at residential of Citra Pesona Indah and Metro Palu Regency. This research was conducted by studying literature that can support this research, gathering data using sampling techniques (stratified random sampling) with the formula of Slovin, conducting interviews and questionnaires to the respondents, analyzing the data results of the interview to describe the characteristics of the residence occupants and analyzing with the categories that will result in trip generation number on the residential area.Â The number of trip generation obtained by conducting interviews through questionnaires was 1665 movements / day for Citra Pesona Indah and 222 movements / day for Metro Palu Regency. The number of trip generation resulted using category analysis method is 1669.4 movement / day for Citra Pesona Indah and 222.4 movements / day for Metro Palu RegencyKeywords : Trip generation, category analysis, sampling techniques